KH. Ma'ruf Amin's Thoughts on the Development of Sharia Economics in Indonesia - M. Arif Romadhoni; Nanda Alfreda Putri; Lusianah Dhewi Findartika; Mashudi (Penerbit Hellow Pustaka, 2025)
This study aims to analyze and describe the thoughts produced by KH. Ma'ruf Amin in Indonesian sharia economics. This study uses a qualitative research method that is descriptive in nature. With this approach, researchers investigate events, life phenomena of an individual or group which are then presented in the form of descriptive chronological sentences using the library study method with the method of collecting library data, reading and recording and processing research materials. The results of K.H Ma'ruf Amin's thoughts in the development of sharia economics are proven by the leadership of K.H Ma'ruf Amin who began to show clear policies related to the development of sharia economics. K.H Ma'ruf Amin has begun to provide ideas for increasing growth and development in this sector and also intensively fixes several regulations that are considered to have the potential to hinder the policy. K.H Ma'ruf Amin also said that in the future the national economy must be supported by the people's economy, not only supported by a handful of conglomerates.